Decaffeination of coffee by supercritical carbon dioxide extraction - Cambaliza, Edmund J.; Dapit, Marcelo C. III; Macadaeg, Katrina R.; Yan, Robbin Ann P. (College of Engineering, 1999)
Plant location: Luis Aguado, Trece Martires, Cavite -- Return on investment: Before taxes - 41.90%, After taxes - 27.28% -- Total capital investment: Php 138M -- Payback period: 2.14 years -- Break even capacity: 235,302.22 kg/yr -- Break even selling price: Php 0.416/g -- Proposed selling price: Php 0.430/g -- Plant capacity: 13,626.62 kg coffee per day